Stevens‐Johnson syndrome and toxic epidermal necrolysis‐like cutaneous presentation of chikungunya fever: A case series. Issue 3 (24th March 2018) - Garg, Taru; Sanke, Sarita; Ahmed, Riaz; Chander, Ram; Basu, Srikanta
Abstract: Chikungunya fever is a benign, self‐limiting, acute viral illness. An epidemic occurred in New Delhi, India, in August and September 2016. We observed many cases with atypical cutaneous features mimicking Stevens‐Johnson syndrome and toxic epidermal necrolysis during this epidemic, especially in infants and children. Twenty‐one children (13 [61.9%] boys, 8 [38%] girls) presenting with vesico‐bullous and necrotic lesions were reviewed. Cutaneous presentation included vesicles and bullae with purpuric macules and necrosis, seen in 16 (76%) patients. Skin lesions resolved in 5‐7 days, leaving behind hyperpigmentation in seven (33.3%) patients and hypopigmentation in three (14.2%). Minor oral erosions were observed in three (14.2%) patients, and palmoplantar erythema was seen in four (19.04%). It is essential for dermatologists to understand the Stevens‐Johnson syndrome and toxic epidermal necrolysis‐like presentation of chikungunya and not to misinterpret it as true Stevens‐Johnson syndrome and toxic epidermal necrolysis, which will lead to unnecessary intervention and management.